Islam and Democracy: The Failure of Dialogue in Algeria by Frederic Volpi (London: Pluto Press, 2003. 168 pages.) (American Journal of Islam and Society, 2003)
In all of the Middle East and North Africa, Algeria was the first country to be infected by the wind of democratization that swept the developing world in the 1980s and 1990s. The country became a political laboratory for the rest of the Arab world, as liberalization opened spaces for moderate and radical Islamic groups to contest elections. Unfortunately, these elections quickly descended into a long drawn-out and brutal war with the secularist rulers. This bitter battle, fought most fiercely between 1992-99, turned Algeria into a hot spot, thereby raising the question of whether democracy is feasible in the Muslim world. Frederic Volpi's new book seeks to answer this question by analyzing the process of political liberalization and the severe problems it generated in Algeria. Volpi presents early and mid-twentieth-century North African scholars' reinterpretations of the Islamic creed that activated the emergence of anti-secularist movements in the Maghreb as a point of departure for his historical narrative of the Algerian conflict. Although Algeria's militant movement was coopted by the state party (the National Liberation Front [FLN]) and lost its dynamism during the post-independence years, it still sought to change the political system by operating from the community level, where it had built a network of associations. The author shows how this network's provision of services designed to meet the people's welfare needs helped thrust Islamic leaders into the political limelight as they utilized their organizational capacities and authority to transform the 1988 October food riots into a political protest ...